STUDI EVALUATIF TENTANG KUALITAS PELAKSANAAN MANAJEMEN BERBASIS SEKOLAH DI SD KABUPATEN BULELENG - I Made Ariasa Giri (Purwadita : Jurnal Agama dan Budaya, 2019)
This study aims to measure the quality of implementation of school-based managementin Elementary School Buleleng Regency as well as knowing the obstacles faced. This researchapproach uses empirical research (post facto). The study sample was 75 people. Data collectionon the evaluation of the quality of the implementation of school-based management in ElementarySchool Buleleng Regency was carried out using the questionnaire method. The collected data isthen analyzed through editing, coding and tabulation, then a conclusion is drawn based on theT-test transformation in the form of code min (-) and plus (+) which is then inserted into theGlickman quadrant. The results showed that: (1) The quality of the implementation of schoolbasedmanagement in BulelengRegencyElementarySchoolwasseenfromthecontextvariablewithafrequencyof53.33%positivecategory,(2)Thequalityofimplementingschool-basedmanagementinSDBulelengRegencywasseenfromtheinputvariablewithapositivecategoryfrequency62.67%,(3)Thequalityoftheimplementationofschool-basedmanagementinBulelengRegencyElementarySchoolisseenfromtheprocessvariablewithapositivecategoryfrequency70.67%(4)Thequalityofimplementingschool-basedmanagementinSDBulelengRegencyisseenfromproductvariableswithapositivecategoryfrequency60%.